Theory in Action: Public Health and Community Power Building for Health Equity. Issue 1 (January 2023) - Heller, Jonathan C.; Little, Olivia M.; Faust, Victoria; Tran, Paula; Givens, Marjory L.; Ayers, Jeanne; Farhang, Lili
Abstract : Context: Within the field of public health, there is growing awareness of how complex social conditions shape health outcomes and the role that power plays in driving health inequities. Despite public health frameworks lifting up the need to tackle power imbalances to advance equity, there is little guidance on how to accomplish this as an integral part of health promotion. Objective: This article addresses the need for public health professionals to better understand power and identifies opportunities for shifting power to achieve more equitable outcomes. First, it defines power and community power building. Next, it reviews a pragmatic theoretical framework that organizes power into 3 faces: (1) exercising influence in formal decision-making processes; (2) organizing the decision-making environment; and (3) shaping worldviews about social issues. Finally, it connects each face of power to community power-building practices using concrete examples. Implementation: This article highlights real-world case examples to demonstrate how theory translates to action by describing how public health practitioners in government, academic, and nonprofit settings incorporate the 3 faces of power into their work. The case examples illustrate how public health organizations and practitioners can partner with those most impacted by inequities to help shape decision making, agenda setting, and worldviews to influence policy and practice toward more equitable outcomes. Discussion: The public health field can learn from and build on these innovative examples to establish new practices, scale up promising approaches, and evaluate what works to shift power for the greater good.